THE ESSENCE OF POSITION OF ADVERBIAL MODIFIERS IN THE DISCOURSE - Uzokova, Shakhnoza (Журнал иностранных языков и лингвистики, 2021)
This article investigates one of the discourse functions that has been proposed for the variation in English of the position of adverbials within the clause. Objective methods are used to measure persistence of adverbial scope and how scope is cancelled. The cohesive role of adverbials is discussed with the help of a particular cohesive relation.